EFFECT OF DIFFERENT CLEANING PROCEDURES ON THE SURFACE ROUGHNESS OF VACUUM-FORMED RETAINER MATERIALS - Zsuzsanna Bardocz-Veres; Bence Mátyus; Gyula Mátyus; Gabriela Strnad; Bernadette Kerekes- Máthé (Romanian Society of Oral Rehabilitation, 2024)
Background: The use of diverse transparent Vacuum-Formed Retainers (VFR) is widespread. However, there is a lack of detailed instructions regarding the proper cleaning methods for patients to ensure optimal longevity and plaque removal from their retainers. The objective of our study was to investigate the alteration in surface roughness of polypropylene (PP), thermoplastic polyurethane (TPU), polyethylene terephthalate glycol (PET-G), and co-polyester (COP) materials exposed to different cleaning procedures. Methods: In the initial phase of our study, we distributed a questionnaire to individuals who utilize vacuum-formed retainers to gain insight into their cleaning practices. After consolidating the results, we established six different cleaning categories. A toothbrush simulator, designed and built by one of the authors (B.M.), was used to simulate brushing for 30 days. A profilometer was used to quantify the inner surface roughness (Ra). Statistical analysis included Kruskal-Wallis, ANOVA, Post hoc analysis and t-tests. Results: The findings of our study demonstrated that distinct cleaning protocols had varying effects on the retainer materials. TPU samples typically exhibited a reduction in surface roughness following most cleaning procedures, but PP samples demonstrated an elevation in roughness. COP proved to be the most resistant material, and TPU the least. Medium and electric toothbrushes and whitening toothpaste should be used with caution. Conclusions: These findings emphasize the significance of choosing the appropriate cleaning procedures to preserve the integrity and hygiene of VFR materials, ultimately enhancing patient satisfaction.